The Compliance-Based Coffee Growers of Bondowoso on Regent Amin Said Husni in the Culture of Madurese Society - Latifatul Izzah; Singgih Tri Sulistiyono; Yety Rochwulaningsih; Dewi Salindri; Sri Ana Handayani; Jani Januar; Neneng Afiah (Institut Agama Islam Negeri Madura, 2019)
This study discussed the compliance of the coffee farmers particularly in Sumberwringin Bondowoso against the figure Amin Said Husni. The Regent concerns for the fate of the coffee farmers and public welfare in Bondowoso cannot be inseparable from the religious life of the Regent; implementing policies based on the principles of the Islamic religion. This study aimed to answer the question regarding the causes of the emergence of people’s compliance with coffee farmers to switch the Arabica coffee plant according to the instructions given by the Regent. This study applied the habitus concept developed by Pierre Bourdieu and sharpened using the historical method. The studied population was coffee farmers at district of Sumberwringin (Sukorejo, Rejoagung and Sumberwringin village). This study found that the compliance of the coffee farmers could attract people who originally planted Robusta switched to Arabica coffee as their Regent’s instruction. The compliance of coffee farming communities (majority of Madurese) was hierarchical obedience that became a necessity to be actualized in daily praxis as “normative” binding. The compliance of produce luck to economic conditions as well as improving the welfare of coffee farmers, because the selling price of Arabika is higher than the Robusta coffee.